Determinants of understanding and satisfaction with health education by patients in primary healthcare - Galadari, Alaa; Alnaqbi, Jawaher; Al Mansoori, Muath; Darwish, Ebtihal; Khan, Fozia (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Objectives: The aim of the study is to measure the percentage of patients receiving health education services regarding diagnosis, treatment, prevention, health promotion, and its relation to the satisfaction level in primary healthcare (PHC) centers in Abu Dhabi, United Arab Emirates. Patients and Methods: This is a cross-sectional study using a questionnaire targeting the population aged 18 and above who attend PHC centers in Abu Dhabi Island. A total number of 333 participants were enrolled in this study. Results: About 89.6% of participants reported receiving health education regarding diagnosis, treatment, prevention, and health promotion. 81% of health education was delivered by the physician using verbal methods, 94.4% of the participants reported it to be the most preferred method. A relationship was found between health education and satisfaction level (P = 0.000). 86.4% were satisfied with the health education service they received. The main reasons of satisfaction included provider medical knowledge 43.6% and good communication skills 41.2% (P = 0.045). A correlation was found between patient satisfaction and the continuity of care of participants as 88.2% who are satisfied reported will revisit the same physician (P = 0.000). Conclusions: Majority of the patients received health education about diagnosis, treatment, prevention, and health promotion. Most of them preferred a verbal method to be delivered by a physician. Moreover, participants who received health education found to be more satisfied and complaint with their follow-up as well as recommend the physician to others. The main reason for dissatisfaction was the provider's poor medical knowledge and poor communication skills. Therefore, physicians may need training courses to achieve better communication skills and to improve medical knowledge delivered to patients.
Keywords: Abu Dhabi Island; health education; primary health care; satisfaction; United Arab Emirates